Enthesis erosion in spondyloarthritis is not a persistent structural lesion. Issue 11 (27th August 2011) - de Miguel, Eugenio; Falcao, Sandra; Castillo, Concepción; Plasencia, Chamaida; García, Miriam; Branco, Jaime C; Martín-Mola, Emilio
Abstract : Objective: To evaluate the ability of ultrasound (US) to detect the presence and change of Achilles erosions in spondyloarthritis (SpA). Methods: A blind prospective two-dimensional (2D) and three-dimensional (3D) US study of Achilles enthesis erosions in early SpA was undertaken. US examinations were performed at baseline and at 6 and 12 months of follow-up. Clinical outcomes measures were collected. Results: Bilateral Achilles entheses of 68 patients (35 women) were investigated. The mean Bath Ankylosing Spondylitis Disease Activity Index and C reactive protein (CRP) levels were 4.58±2.05 and 5.97±9.91 mg/l, respectively. The κ values for intrareader agreement for 2D and 3D images were 0.84 and 0.85 for two readers. 2D US visualised 10 erosions (7.4%) and 3D US visualised 13 erosions (9.6%) in 10 patients (14.7%). At 6 and 12 months of follow-up, 25% and 50% of basal erosions had disappeared, respectively and, of the new erosions that appeared at 6 months, 40% had disappeared 6 months later. A statistically significant association between erosion and CRP levels, entheseal Doppler signals and the number of tender and swollen joints was found. Conclusions: US examination of Achilles erosions is reliable and sensitive to change. An association was found between Achilles erosions and objective activity-based measurements of SpA outcomes.